2017
DOI: 10.4103/njcp.njcp_14_16
|View full text |Cite
|
Sign up to set email alerts
|

Ureterolithiasis: Management in an environment with limited facilities

Abstract: Management of ureteric stones in our environment is affected by delay in presentation, low level of awareness of urinary stone disease, lack of modern endourological equipment, and paucity of urological surgeons. Finally, medical treatment should be explored for stones below 10 mm in size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 0 publications
5
16
1
Order By: Relevance
“…The sizes of stones managed in the series ranged from 5–95 mm. 16 , 23 , 47 , 49 The rate of open surgery for upper tract urolithiasis was about 69.5% in the review with nephrolithotomy 20.8%, pyelolithotomy 37.9%, ureterolithotomy 29.9% and nephrectomy 7.9%. Authors from Senegal (Diallo et al; /Kane et al) 11 , 12 and Kenya (Ngugi et al; Wathigo et al) 19 , 20 reported a considerable use of endoscopic surgery for upper tract urolithiasis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sizes of stones managed in the series ranged from 5–95 mm. 16 , 23 , 47 , 49 The rate of open surgery for upper tract urolithiasis was about 69.5% in the review with nephrolithotomy 20.8%, pyelolithotomy 37.9%, ureterolithotomy 29.9% and nephrectomy 7.9%. Authors from Senegal (Diallo et al; /Kane et al) 11 , 12 and Kenya (Ngugi et al; Wathigo et al) 19 , 20 reported a considerable use of endoscopic surgery for upper tract urolithiasis.…”
Section: Resultsmentioning
confidence: 99%
“…of Patients Mean Age (years) Age Range (years) Percent of Male to Female Type of Stone Stone Location Diallo et al Senegal 11 2008–2012 52 42.7±5.2 13–70 M: 66.7% F: 33.3% N/A Renal: 38.2% Ureteral: 61.8% Kane et al Senegal 12 2009–2013 89 44.0 4–75 N/A N/A Renal: 50.9% Ureters: 49.4% Odzebe et al Congo Brazzaville 13 2000−2004 68 52.1 14–82 M: 76.5% F: 23.5% N/A Renal: 29.4% Ureters: 1.5% Bladder: 69.1% Odzebe et al Congo Brazzaville 14 2002–2013 71 9.1 0.2–15 M: 67.6% F: 32.4% Calcium oxalate 26.4%, struvite 13.2%, calcium phosphate 9.4% Renal: 36.8% Ureters: 7.9% Bladder: 46.1% Omisanjo et al Nigeria 15 2012–2016 76 49.1±16.3 2–84 M: 64.5% F: 35.5% N/A Renal: 36.8% Ureters: 7.9% Bladder: 48.7% Odoemene et al Nigeria 16 2007–2014 69 40.4 8–72 M: 76.8% F: 23.2% …”
Section: Resultsmentioning
confidence: 99%
“…Patients presenting with acute renal colic at the emergency department Authors Year Country Study design No. of patients % Male Mean age ± SD (years) Kim et al [ 13 ] 2018 South Korea Retrospective, observational 798 68.6 48.2 ± 13.3 Desai et al [ 14 ] 2018 USA Retrospective, observational 350 NR NR Türk and Ün [ 15 ] a 2017 Turkey Prospective, observational 516 60.5 37 ± 20.3 Shrestha et al [ 16 ] a 2017 Nepal Retrospective, observational 201 55.2 29 ± 13.5 Odoemene et al [ 17 ] a 2017 Nigeria Prospective, observational 69 76.8 40.4 ± 2.9 Mefford et al [ 18 ] 2017 USA Retrospective, observational 393 69 Median 43 (IQR 32–54) Rapp et al [ 19 ] 2016 USA Retrospective, observational 613 47 49 ± 0.6 Park et al [ 20 ] 2016 South Korea Prospective, RCT 103 66 45.6 ± 12.55 Hernandez et al [ 21 ] 2016 USA Retrospective, observational 536 56 45.9 ± 16.3 <...>…”
Section: Resultsmentioning
confidence: 99%
“…Definition of microhematuria was different among the included studies. Six studies included also patients presenting with macroscopic hematuria [14,17,19,22,26,50]. Details on the microhematuria test are reported in Table 2.…”
Section: Selected Studiesmentioning
confidence: 99%
“…De nition of microhematuria was different among the included studies. Six studies included also patients presenting with macroscopic hematuria [14,17,19,22,26,50]. Details on the microhematuria test are reported in Table 2.…”
Section: Selected Studiesmentioning
confidence: 99%